Gender Dynamics in Islamic Law Perspective: Descriptive Study in Idaman Village, Banten - Tolkah Tolkah (Budapest International Research and Critics University, 2021)
Gender differences and cultural structures in the ideal village area classify the status of men and women. Islamic law has a different point of view in seeing gender status in Indonesian society. This study looks at the dynamics of gender in the village of ideal banten from the perspective of Islamic law. This study used a descriptive method with a qualitative approach, while the determination of the informants was purposvie sampling by considering traditional leaders, village heads and communities and finally data collection through primary and secondary. The results showed that gender dynamics inequality as a problem in the Islamic world, as well as the dark side of masculine-related behaviors cannot only be approached through the perspective of women alone.